2017
DOI: 10.7567/jjap.56.081203
|View full text |Cite
|
Sign up to set email alerts
|

Performance degradation of InGaP solar cells due to 70 keV electron irradiation

Abstract: The performance of InGaP solar cells irradiated with electron beams at energies lower than the damage threshold is degraded. To investigate the irradiation effect, GaAs and InGaP solar cells are irradiated with 70 keV electron beams. Measurements of the electroluminescence and external quantum efficiency, in addition to the light current voltage measurement, are conducted. The results show that the performance of the InGaP solar cell, mainly open-circuit voltage, is degraded and affected by nonradiative recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In studies focusing on the DDD model, the effect of a change in the value of E d on the accuracy of degradation prediction has been frequently confirmed via irradiation tests, using high-energy electrons (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The E d of phosphorus is reported to be approximately 9 eV in the InGaP solar cells.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In studies focusing on the DDD model, the effect of a change in the value of E d on the accuracy of degradation prediction has been frequently confirmed via irradiation tests, using high-energy electrons (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The E d of phosphorus is reported to be approximately 9 eV in the InGaP solar cells.…”
Section: Introductionmentioning
confidence: 98%
“…5) However, in our previous studies, it was observed that electrons at 60 keV generate radiation-induced defects resulting from the recoil of phosphorus atoms and thus cause the degradation of InGaP solar cells. [6][7][8] This unexpected degradation is probably caused by the incorrect value of displacement threshold energy (E d ) in NIEL.…”
Section: Introductionmentioning
confidence: 99%
“…25) Previously, one of the authors used different displacementdamage threshold energies for Cu, In, Ga, and Se. 26,27) However, the differences in the calculated NIEL values are less than 20% for electrons and less than 2% for protons and He + ions. We confirmed that these differences do not significantly affect the analysis described in the next section.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, we have proposed a radiation measurement system based on dosimetry technology using a solar cell. [2][3][4] Solar cells have structures similar to those of semiconductor radiation detectors. Conventional semiconductor radiation detectors have relatively thick structures because the absorption coefficient of radiation is much smaller than that of sunlight in semiconductors.…”
Section: Introductionmentioning
confidence: 99%